Interior floor finishes preferences of residents in Klang Valley : a preliminary survey / Nurrajwani Abdul Halim, Siti Norlizaiha Harun and Azizul Azli Ahmad - Abdul Halim, Nurrajwani; Harun, Siti Norlizaiha; Ahmad, Azizul Azli (2018)
Residential is a place where human being built and live in and the resident is a person who lives in that place. It can be classified into three levels namely house, home and shelter. Whether it is called house or home or shelter, they play significant role for the human being who live inside them. Therefore, Malaysian construction member especially interior designers should consider the residents’ preferences on interior floor finishes. These preferences are very important to assist the residents to rebuild, recreate and reshape their living environment according to their pleasure, necessities and wishes. This paper discussed the preliminary survey that was conducted to 142 respondents who have renovated their interior spaces. The aims were to detect key features to be addressed in this research, to verify issue and research gap before the research being performed to prove that this research can be done valid and significant as well as to answer the research objectives of the research. There are two objectives of this preliminary survey which are to explore the most chosen types of interior floor finishes towards interior spaces such as living area, dining area, kitchen area, bedroom and restroom. The second objective is to discover the most popular interior floor finishes chosen by the respondents towards the selection criteria of beauty by the respondents in Klang Valley area. This study tested on selected criteria which are beauty, hygienic, durable and comfort. Nevertheless, this research only selected criteria of beauty towards interior floor finishes such as tiles, timber floor board, carpet, mosaic, marble, vinyl and others were discussed. As a conclusion, the residents do renovation with the purpose of rebuilding, recreate and reshape their living environment particularly their interior surrounding to fulfil their satisfaction, needs and desires. Therefore, all the construction members should work hand in hand to accomplish the residents’ living environment.